Efficacy of Different Progestins in Women With Advanced Endometriosis Undergoing Controlled Ovarian Hyperstimulation for in vitro Fertilization-A Single-Center Non-inferiority Randomized Controlled Trial - Guo, Haiyan; Li, Jianghui; Shen, Xi; Cong, Yanyan; Wang, Yun; Wu, Ling; Li, Bin; Gao, Hongyuan; Ma, Meng; Zhang, Wei; Mao, Xiaoyan; Fu, Yonglun; et al. (Frontiers in Endocrinology, 2020)
Methods: 450 infertile patients with severe endometriosis undergoing IVF/ICSI were randomized to: medroxyprogesterone acetate +hMG; dydrogesterone+hMG; and progesterone +hMG. Ovulation was induced with a gonadotropin-releasing hormone agonist (GnRH-a) and chorionic gonadotropin (hCG). Viable embryos were cryopreserved for later transfer.The primary endpoint outcome was the number of oocytes retrieved. Secondary indicators included the incidence of a premature surge in luteinising hormone (LH), the number of viable embryos, and clinical pregnancy outcomes.The number of oocytes retrieved was higher in the medroxyprogesterone acetate +hMG group than the two other groups (9.3±5.7 vs. 8.0±4.5 vs. 7.8±5.2, P=0.021). LH levels were suppressed after a 6-day progestin treatment in the medroxyprogesterone acetate +hMG and dydrogesterone+hMG groups, but there was a rebound of LH values in the progesterone +hMG group. No premature LH surge and ovarian hyperstimulation syndrome (OHSS) occurred. The interval from trigger to oocyte retrieval and rate of oocyte retrieval were slightly lower in the progesterone group than that in the two other groups. No significant differences among the three groups were observed in fertilization and pregnancy outcomes.It is mandatory to point out that our conclusions are valid for patients with ovarian advanced endometriosis but normal ovarian functions. These results suggest effective methods to achieve clinical pregnancy in women with endometriosis and normal ovarian function. These methods could be tested with other populations of women with endometriosis.